Effect of Polyurethane Foam Addition to Flatwise Compressive and Sound Absorption Properties of 3D Woven Sandwich Glass Fiber â Polyester Composite - Tiara Sayyu, Chairani
3D woven sandwich composite has good delamination strength, but has low flatwise compressive properties. This sandwich composite will be used as a light rail transit’s panel in Indonesia. In this application, it is required to have a good flatwise compressive and sound absorption properties. In this research, the effect of polyurethane foam addition and core’s density variation to flatwise compressive properties and sound absorption properties were studied. Sandwich composite 3D woven was made by using wet hand lay-up and polyurethane foam was added by using injection. Inspection of core’s construction was done by stereo microscope and inspection of foam’s structure was done by scanning electrone microscope. Flatwise compressive properties were evaluated by compression test and sound absorption properties were also evaluated by impedance tube test. Addition of polyurethane foam to 3D woven sandwich composite with thickness of 6 mm succeed in improving core’s density up to 25%. Addition of foam to sandwich composite improved flatwise compressive strength and modulus up to 345% and 254%, respectively, with maximum flatwise compressive strength and modulus of 5.87 MPa and 8.99 MPa, which obtained by sandwich composite with highest core’s density. Addition of polyurethane foam also improved noise reduction coefficient and sound absorption average of sandwich composite up to 60% and 14%, respectively.